Implikasi Hukum Terhadap Peran Notaris Pada Pembatalan Perjanjian Pengikatan Jual Beli (PPJB) Hak Atas Sebidang Tanah Pada Putusan Mahkamah Agung Nomor 959 PK/Pdt/2023 - Pujawati, Resiyana Nurmalia (JURNAL PENELITIAN SERAMBI HUKUM, 2026)
The sale and purchase transaction of a plot of land is a legal event regulated by law, where the binding can be carried out before an authorized official, in this case a notary, who is authorized to make an authentic deed related to the transfer of land rights and/or legal ownership rights. The creation of rights and obligations that are built or bound by each party, the seller and buyer, is the main thing that must be implemented so that the deed that was originally an agreement becomes a valid deed of sale and purchase. This study aims to examine legal certainty in the settlement of a sale and purchase transaction of a plot of land in a case study of the Supreme Court decision Number 959 PK/Pdt/2023 in which a Notary from Bengkulu City is a party involved. The research method used is a normative legal method that focuses on the study of Laws and Regulations, and other secondary data that supports the case of a land sale and purchase agreement. In fact, unfulfilled sales and purchase transactions result in legal uncertainty arising from it so that the parties withdraw and the agreement can be canceled as stated in the agreement deed Number 76 in the case study of the Supreme Court decision Number 959 PK/Pdt/2023. A notary is one of the most important parties in determining the validity of a Sale and Purchase Deed.